1979
DOI: 10.1111/j.1744-6570.1979.tb02154.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Psychological Influence: An Illustration of the Psychological Climate Approach to Work Environment Perceptions

Abstract: Correlates of subordinates' perceptions of their psychological influence on supervisors' decisions were examined for 126 subordinates in high technology jobs and 205 subordinates in low technology, production line jobs. Based on the psychological climate perspective of work environment perceptions, it was predicted that perceptions of psychological influence would be related significantly to (a) situational attributes, including supervisor behaviors, (b) individual characteristics, and (c) person by situation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
58
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 64 publications
3
58
0
Order By: Relevance
“…However, an inspection of the correlation of variables' matrix shows that the relationships among the variables varied; thus common method variance was probably not responsible for our results [40]. Finally, our study involved a suite of Internet applications, not just one.…”
Section: Limitationsmentioning
confidence: 47%
“…However, an inspection of the correlation of variables' matrix shows that the relationships among the variables varied; thus common method variance was probably not responsible for our results [40]. Finally, our study involved a suite of Internet applications, not just one.…”
Section: Limitationsmentioning
confidence: 47%
“…He reported that the organizational climates of dierent school districts and Peace Corps training units could be predicted from the average of the psychological needs expressed by their members. At the individual level of analysis, research has also revealed relationships between such needs as achievement motivation and growth need strength with job perceptions, psychological in¯uence, job involvement, organizational commitment, desire to leave, and performance (Hackman and Oldham, 1975;James et al, 1979;Steers and Braunstein, 1976). This body of theory and research suggests that individuals with comparable levels of need strength will interpret organizational events similarly.…”
Section: Need Strengthmentioning
confidence: 91%
“…Following a common practice in early stages of theory development (e.g., Brown and Leigh, 1996;May et al, 2004), we examine the construct definition of psychological climate for communication safety to identify appropriate antecedent, dependent and moderator variables. Future research needs to evaluate the theoretical implications of our findings to confirm the validity of our theorizing.Future research should also examine how dispositional factors moderate the effects of 27 contextual factors on psychological climate, as James et al (1979) proposed that 'two forms of moderation were involved, namely moderation due to differences among individuals and moderation due to differences among situations' (p. 569). The current research highlights the dispositional approach, and we treat harmony motives as independent variables and job autonomy as a moderator.…”
mentioning
confidence: 99%
“…More specifically, our research develops a model based on prior theorizing of psychological climate (e.g., James et al, 1978;James et al, 1979;James et al, 2008) Figure 1 for the research model proposed.…”
mentioning
confidence: 99%
See 1 more Smart Citation